2005
DOI: 10.1021/ma048941+
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length Dependence of Chain Propagation Revisited

Abstract: On the basis of recently developed numeric procedures, the results obtained for the propagation constants kp by means of the PLP-SEC method (pulsed laser polymerization followed by size exclusion chromatographical analysis of the chain length distribution) were subjected to a critical reevaluation and reanalysis particularly with respect to the chain length dependence of k p. In this context the errors arising from a broadening caused by axial dispersion in the SEC were largely eliminated together with other u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…Thus the chain length dependence of the k p values can not only be compared directly for the two polymerization systems but can also be compared with the data published by Willemse et al [2] The filled diamonds (triangles) represent the results for the polymerization in microemulsion (solution) as deduced from the location of the point of inflection on the low molecular weight side; the full squares (inverted triangles) represent the data obtained from the peak maximum. All four data sets show the same general trend of a chain length dependence persisting to higher chain lengths as was already shown by Olaj et al [1,24] In order to make sure that BB can be excluded as a possible source for discre- The corresponding open symbols represent the results after application of the correction (Equations (7a) and (7b)). The CLD function calculated according to Equation (8) is included as full and broken curve, respectively, which are only shifted by the constant value as indicated.…”
Section: Resultssupporting
confidence: 71%
“…Thus the chain length dependence of the k p values can not only be compared directly for the two polymerization systems but can also be compared with the data published by Willemse et al [2] The filled diamonds (triangles) represent the results for the polymerization in microemulsion (solution) as deduced from the location of the point of inflection on the low molecular weight side; the full squares (inverted triangles) represent the data obtained from the peak maximum. All four data sets show the same general trend of a chain length dependence persisting to higher chain lengths as was already shown by Olaj et al [1,24] In order to make sure that BB can be excluded as a possible source for discre- The corresponding open symbols represent the results after application of the correction (Equations (7a) and (7b)). The CLD function calculated according to Equation (8) is included as full and broken curve, respectively, which are only shifted by the constant value as indicated.…”
Section: Resultssupporting
confidence: 71%
“…[15,16] More recently, SEC broadening and its influence on k p determination was addressed by van Herk, [75][76][77] as well as by Olaj and Schnöll-Bitai. [78][79][80][81][82] In PLP experiments, an evenly spaced sequence of laser pulses, mostly at a UV wavelength, is applied to the reaction system containing monomer and a photoinitiator. As discussed by García and coworkers, in particular at high laser pulse repetition rates and/or high energy per laser pulse, special care has to be taken to avoid a temperature increase during pulsing.…”
Section: Sabine Beuermann Is Professor Of Polymermentioning
confidence: 99%
“…[4] A recent re-evaluation of the experimental data of reference [3] by Olaj et al confirmed their former conclusion that the long-range chain-length dependence of k p extends over several hundreds of propagation steps. [5] Olaj et al explicitly reject the alternative view of Willemse et al that only the k p data for extremely short chains are responsible for this chain-length dependence.…”
Section: Introductionmentioning
confidence: 96%